Comparative evaluation of the effect of different cleaning methods on sealant penetration and nanoleakage / Khairunnisa Ahmad Bustami - Khairunnisa, Ahmad Bustami (2018)
Background: Fissure sealant prevents initiation and progression of occlusal caries by acting as a physical barrier that inhibits accumulation of microorganisms and food debris in pits and fissures. Proper cleaning and fissure preparation are necessary prior to sealant placement. Hence, the occlusal surface must be free from plaque, acquired pellicle, and debris that might interfere with the etching process or sealant penetration. The objectives of this study were to compare the effect of occlusal surface cleaning methods using either a toothbrush or a rotary brush prior to sealant placement on sealant penetration depth and nanoleakage occurrence, and to assess the influence of fissure type/morphology on sealant penetration. Methods: Thirty-three sound extracted human maxillary premolars were randomly divided into three groups of different cleaning methods prior to fissure sealant placement: (1) No cleaning of the occlusal surface (control), (2) occlusal surface cleaned with a toothbrush for 10 seconds, and (3) occlusal surface cleaned with a rotary brush attached to a slow-speed handpiece for 10 seconds. The teeth were mounted on epoxy resin, sectioned into halves before being stained with modified silver staining technique, and polished. Depth of sealant penetration was determined using scanning electron microscopy (SEM) according to the scoring method: (1) sealant penetrated one-third of the total fissure length, (2) sealant penetrated half of the total fissure length, and (3) sealant penetrated the total fissure length. Fissure type/morphology was classified into U-type, V-type; Y1-type and Y2-type. Nanoleakage expression along sealant-enamel interface was determined by measuring silver nitrate uptake using EDX. Data management and analysis were performed using SPSS version 23. Different cleaning methods were compared using Fisher‘s exact test (sealant penetration) and Kruskal-Wallis (nanoleakage). Association between fissure type/morphology and sealant penetration was determined using Fisher‘s exact test. The test was considered significant when p<0.05. Results: The occlusal surfaces cleaned with a rotary brush has the highest percentage (18%) of sealant penetration with score 3 followed by the occlusal surfaces cleaned with a toothbrush (15%) and no cleaning of the occlusal surface (12%). Higher mean rank of nanoleakage expression (91.4) was found in the control group followed by toothbrush group (81.0) and rotary brush group (76.5). However, no significant association was observed between the different cleaning methods (toothbrush and rotary brush); and the sealant penetration and nanoleakage expression (p>0.05). The only significant difference was observed between fissure type/morphology and sealant penetration depth (p=0.025). Conclusions: In conclusion, cleaning of the occlusal surface prior to sealant placement using a toothbrush is as effective as a rotary brush in relation to sealant penetration and occurrence of nanoleakage. Hence, toothbrush can be used as one of the cleaning methods on the occlusal surface prior to fissure sealant placement.